-58x-2+6=8x-230.6

Simple and best practice solution for -58x-2+6=8x-230.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -58x-2+6=8x-230.6 equation:


Simplifying
-58x + -2 + 6 = 8x + -230.6

Reorder the terms:
-2 + 6 + -58x = 8x + -230.6

Combine like terms: -2 + 6 = 4
4 + -58x = 8x + -230.6

Reorder the terms:
4 + -58x = -230.6 + 8x

Solving
4 + -58x = -230.6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
4 + -58x + -8x = -230.6 + 8x + -8x

Combine like terms: -58x + -8x = -66x
4 + -66x = -230.6 + 8x + -8x

Combine like terms: 8x + -8x = 0
4 + -66x = -230.6 + 0
4 + -66x = -230.6

Add '-4' to each side of the equation.
4 + -4 + -66x = -230.6 + -4

Combine like terms: 4 + -4 = 0
0 + -66x = -230.6 + -4
-66x = -230.6 + -4

Combine like terms: -230.6 + -4 = -234.6
-66x = -234.6

Divide each side by '-66'.
x = 3.554545455

Simplifying
x = 3.554545455

See similar equations:

| 262.818/28.26 | | x(2x-2)+x(2x-4)=(4x+7)(x-3) | | (2x^4+7x^3-8)-(7x^2-5x+4)= | | -2-5x=-2(1+4x) | | 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x | | 0.55=logx | | -4-p=8p-5(6+7p) | | (3xy^2-2y)=0 | | f(2e^4)=lnx | | 2=4-2f | | 81/54 | | 10x-20=-5x+10 | | -15=-k-4k | | x-.15x=7849.08 | | 4a^2-6a^6/8a^-3 | | x+6+3x=-18 | | 6-14=z/-4 | | 30+.5x=1.25x | | x+(-7)=-77 | | x-.15x=4812.96 | | 4.25z=4.5z-6.25+6.25 | | x^2+4x+8y+1=0 |

Equations solver categories